PENGARUH Indole Butyric Acid DAN Naphtaleine Acetic Acid TERHADAP INDUKSI PERAKARAN TUNAS PIRETRUM [Chrysanthemum cinerariifolium (Trevir.)Vis.] KLON PRAU 6 SECARA IN VITRO - Rostiana, Otih; Seswita, Deliah (Buletin Penelitian Tanaman Rempah dan Obat, 2007)
Effects of Indole Butyric Acid and Naphtaleine Acetic Acid on the root-induction of pyrethrum [Chrysanthemum cinerariifolium (Trevir.)Vis.] clone Prau 6 in vitroPyrethrum is one of botanical pesti-cides producing plant that has beneficial va-lue to be improved as the substitution of syn-thetic pesticide, which is considered to be harmful for both of human and environment. In order to obtain a sufficient planting mate-rial, in vitro propagation had been performed. Rooted-shoots derived from in vitro cultured adapted better than that of un-rooted one, when transplanted into the field (acclima-tization). Therefore, in this research root in-duction of pyrethrum clone Prau 6-in vitro-shoots were conducted by applying Indole Butyric Acid (IBA) and Naphtaleine Acetic Acid (NAA). Experiment was arranged in a single factor Completely Randomized Design with 10 replications. The treatment tested was an application of synthetic auxins (IBA or NAA) into MS medium in 5 different level of concentrations (0.2; 0.4; 0.6; 0.8; 1.0 mg/l), and control (without auxin). The parameters observed were time to root-initiation, number and length of root, and root characteristic, at 6 weeks after subcultured. The results showed that application of IBA or NAA into MS me-dium significantly affected to the root initia-tion time, number of root, length and charac-teristic of the root, 6 weeks after subcultured. Induced-root on the medium containing 0.2 mg/l IBA showed a better characteristic as compared to others treatments with rounded-form, shorter initiation time (12.5 days), large amount of root (14.1) and longer (1.47 cm).Â